95.1k views
5 votes
Which is a solution to (X - 3)(x + 9) = -27?

User Hank X
by
6.1k points

2 Answers

3 votes

Answer:

Answer is C

Explanation:

EDG2021

User Naqib Hakimi
by
5.7k points
3 votes

Answer:


x_(1) =0\\\\x_(2)=-6

Explanation:

We apply distributive property to the polynomial:

(X - 3)(x + 9) = -27

x*x+9*x-3*x-3*9=-27


x^(2) +9x-3x-27=-27


x^(2) +6x-27+27= 0


x^(2)+6x+0=0

we will use the quadratic formula

x=
\frac{-b+-\sqrt{b^(2)-4*a*c}}{2*a}

a=1 b=6 c=0

we have:

X=
\frac{-6+-\sqrt{6^(2)-4*1*0}}{2*1}

x=
(-6+-√(36))/(2)

X=
(-6+-6)/(2)

so we have


x_(1) =(-6+6)/(2)


x_(2) =(-6-6)/(2)

finally we have


x_(1)=0


x_(2)=-6

User Glen Selle
by
5.5k points